POETRY CONTENT FĪ AL-MAṪ ‘AM IN ANTHOLOGY HAMMUKA DĀIM - Muhammad Naufal Annabil (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
This study aims to reveal the content of the poem Fī al-Mat'am in the anthology Hammuka Dāim. Fī al-Mat'am's poem in Hammuka Dāim contains various sign systems so that semiotic theory is used to reveal the various meanings tucked away in the poem. The method used is the semiotic method of Michael Riffaterre which includes indirect expression and semiotic reading which consists of heuristic reading and hermeneutic reading. This study uses reading and note-taking techniques to collect data. After doing research, it was found that the content of the poem F al-Mat'am in the anthology of Hammuka Dāim is that in loving someone, sincerity and determination are needed, not only dwelling in an expression through the word love itself.